Gender Representation: A Survey of Public Sector English Textbooks of Grades 7 and 8, KP, Pakistan - Hussain, Turab; Umar, Hazrat; Khan, Iftikhar; Batool, Irum (Journal of Communication and Cultural Trends, 2023)
Gender representation in textbooks helps to develop the students’ perceptions of gender construction. It gradually becomes ingrained in students, and they develop their perspectives on gender in society with the help of these textbooks. The represented yardsticks of masculinity and femininity directly impact the gender conception of both male and female students. The current study analyzed gender representation in the newly designed English textbooks taught in Khyber Pakhtunkhwa’s (KP’s) government schools. Using a mixed-method approach, the study analyzed two textbooks, one from grade 7 and the other from grade 8. The linguistic (nouns, noun phrases, pronouns, verbs, verb phrases, adjectives, and adjective phrases associated with male and female constructions) and non-linguistic (invisibility and association of roles with males and females) data was collected, analyzed, and interpreted using textual analysis. The results confirmed the androcentric portrayal of gender in the recently designed English textbooks, which mostly associate females with emotional, friendly, indoor, and dependent activities. On the contrary, it tends to associate males with heroic, intellectual, strong, brave, dominating, decisive, outdoor, and independent qualities. Apart from addressing the issue of education and gender equality, this study has implications for the concerned research community, educational institutions, and the social science disciplines along with the humanities.